Kazimierz Twardowski jako wzór osobowy nauczyciela akademickiego - Zegzuła-Nowak, Joanna (Annales. Etyka w Życiu Gospodarczym, 2012)
The main aim of the article is a justification and attempt to prove the rightness of the thesis that personal features and teaching,educational and pedagogical activity of Kazimierz Twardowski constitute the example of teaching attitude which may be set as a personalmodel for modern team of academic teachers. The attitude of Kazimierz Twardowski proves that the work of a teacher treated as a lifemission is a kind of social service contributing to development of culture and science. For the work of an academic teacher should be basedon realizing of the values, ideals and attitudes socially desired, otherwise the society is threatened with not only stagnation or degradationof science but also arising and developing of attitudes which are socially harmful.